Increase creativity and activity in the creative study of problem solving-based human resource management - Ratna nurdiana; Hadi Suryanto (PPPM STKIP PGRI Lamongan, 2021)
The purpose of this study was to determine whether through cooperative learning method problem-solving type can improve learning outcomes of human resource management in learning human resource management material multiplication and division of fractions and decimals. This research uses two cycles of action research. Each cycle consists of four stages, namely: planning, implementation, observation, and reflection. The target of this research is students who take human resource management courses at PGRI Adi Buana University Surabaya in the 2021/2022 academic year. The data was obtained in the form of formative test results, observation sheets of teaching and learning activities, and interviews. From the results of the analysis, it is known that student learning achievement increases from cycle 1 to cycle 2, namely the average value of the first cycle is 73 learning completeness is 75% and the second cycle the average value is 78.5, and learning completeness is 85%. This increase is also influenced by the level of activity in the creative process which is very good. The collaboration process that occurs produces experience in interacting so that it can improve problem-solving skills through the creative process. The conclusion of this study is that problem-solving methods have a positive effect on increasing student achievement and learning motivation taking human resource management courses at PGRI Adi Buana University in the 2021/2022 academic year, and this learning method can be used as alternative learning in subjects human Resource Management.